2007
DOI: 10.1007/s11262-006-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of immunogenicity of minor envelope protein GP3 of porcine reproductive and respiratory syndrome virus in mice

Abstract: Infections with different viroid species are common among cultivated fruit trees and grapevines, and many old-clone citrus varieties contain up to five citrus viroids (CVds) within a single tree. This paper describes the construction of a CVd-Multiprobe consisting of full-length clones of Hop stunt viroid, Citrus exocortis viroid, Citrus bent leaf viroid and CVd-III. The CVd-Multiprobe was tested against RNA transcripts of the four viroids and RNA extracts from plants singly infected with CEVd or HSVd or multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…After analyzing the degree of antigenic variability in a series of EU isolates using mAbs, it was determined that the C-terminus antigenicity of GP 3 varied greatly among the different EU isolates (Drew et al, 1995). Two replication-defective recombinant adenoviruses expressing GP 3 (rAd-GP 3 ) or truncated GP 3 (rAd-tGP 3 , a hydrophobic region of aa 2-64 was deleted) were constructed and their immunogenicity was tested in mice (Jiang et al, 2007). The mice immunized with recombinant adenoviruses developed PRRSVspecific neutralizing Abs and cellular immune response, including T-cell proliferation responses and cytotoxic T-cell responses, by 2 weeks post-primary immunization.…”
Section: The Minor Glycosylated Envelope Viral Protein Gpmentioning
confidence: 99%
“…After analyzing the degree of antigenic variability in a series of EU isolates using mAbs, it was determined that the C-terminus antigenicity of GP 3 varied greatly among the different EU isolates (Drew et al, 1995). Two replication-defective recombinant adenoviruses expressing GP 3 (rAd-GP 3 ) or truncated GP 3 (rAd-tGP 3 , a hydrophobic region of aa 2-64 was deleted) were constructed and their immunogenicity was tested in mice (Jiang et al, 2007). The mice immunized with recombinant adenoviruses developed PRRSVspecific neutralizing Abs and cellular immune response, including T-cell proliferation responses and cytotoxic T-cell responses, by 2 weeks post-primary immunization.…”
Section: The Minor Glycosylated Envelope Viral Protein Gpmentioning
confidence: 99%
“…The authors also found that ORF7 gene product (N protein) is the most immunogenic protein of PRRSV, but the antibodies induced in sows are non‐protective and may even interfere with protection (Plana Duran et al., ). The immunogenicity of GP3 was further characterized by using two recombinant adenoviruses (rAd), rAd‐GP3 expressing complete GP3 and rAD‐tGP3 expressing truncated GP3 in which amino acids 2–64 were deleted (Jiang et al., ). After mice immunized with the recombinants rAd‐GP3 and rAD‐tGP3, PRRSV‐specific neutralization antibodies, T‐cell proliferation responses and cytotoxic T responses were observed, although the production of neutralizing antibodies was tardy.…”
Section: Experimental Porcine Reproductive and Respiratory Syndrome Vmentioning
confidence: 99%
“…After mice immunized with the recombinants rAd‐GP3 and rAD‐tGP3, PRRSV‐specific neutralization antibodies, T‐cell proliferation responses and cytotoxic T responses were observed, although the production of neutralizing antibodies was tardy. Interestingly, the immune response elicited by rAd‐tGP3 was stronger than that of rAd‐GP3 (Jiang et al., ). The mechanism underlying this phenomenon remains unclear, but it might suggest some adverse factors lie within the deleted sequence of GP3.…”
Section: Experimental Porcine Reproductive and Respiratory Syndrome Vmentioning
confidence: 99%
“…In recent years, non-isotopic molecular hybridization techniques have been used for the simultaneous detection of multiple plant viroids and viruses. This approach has become an attractive method for routine diagnosis due to advantages of low-cost and practicality (Herranz et al 2005;Cohen et al 2006;Aparicio et al 2008;Lin et al 2011).…”
mentioning
confidence: 99%
“…In this study, a non-isotopic dot blot hybridization technique was developed using a polyprobe for the simultaneous detection of four grapevine viroids. Such strategies involving the construction of polyprobes for the simultaneous detection of several viroids have become important for routine diagnosis of viroids due to the reduction of cost, time and labour requirements compared with methods involving detection of individual viroids (Cohen et al 2006;Lin et al 2011). However, the individual viroids resulting in a positive signal using the polyprobe were not distinguished.…”
mentioning
confidence: 99%